Tingkat Kecemasan Ibu Hamil Berhubungan dengan Self Efficacy dalam Melakukan Pemeriksaan Antenatal Care (ANC) - Masta Hutasoit; Celiya Winangrum (Jurnal Indonesia Sehat, 2022)
Background: The COVID-19 pandemic period resulted in a decrease in the number of Antenatal Care visits of pregnant women in health care facilities. The decrease was due to the anxiety of pregnant women being infected and also restrictions on community activities outside. Antenatal care (ANC) examination is useful for early detection of complications of pregnancy and childbirth as the highest cause of maternal mortality. Pregnant women who experience anxiety result in decreased ANC visits and often delays. Self-efficacy of pregnant women is a form of individual self-mediation, in this case pregnant women who are confident can hold beliefs about their expertise to carry out pregnancy checks on health services. Objectives: to identify the relationship between anxiety levels and self-efficacy of pregnant women at the Kasihan I Public Health Center. Methods: This study used a descriptive correlative research design with a cross sectional approach. The sample used in this study were 69 primigravida mothers, which were obtained by non-probability sampling. The research instrument used was the Anxiety questionnaire. Related to Covid-19 transmission for anxiety and Self efficacy/confidence for Self efficacy. Analysis of the data used to see the correlation using somers'd test with <0.05. Results: The results showed that the majority were in the category of not being anxious (95.7%). Data processing with somers'd test obtained p value = 0.045 <0.05, which means that there is a significant relationship between anxiety levels and self-efficacy of pregnant women at the Kasihan I Public Health Center with a correlation value of r = 0.200 (weak). Conclusion: There is a relationship between the level of anxiety related to the transmission of covid-19 with Self efficacy in pregnant women in carrying out ANC. Suggestions for pregnant women in order to get a picture of the importance of self-efficacy for pregnant women, especially in the first pregnancy/primigravida so that mothers can get a good pregnancy and can increase high self-efficacy.